2020
DOI: 10.1002/hsr2.190
|View full text |Cite
|
Sign up to set email alerts
|

A wearable carotid Doppler tracks changes in the descending aorta and stroke volume induced by end‐inspiratory and end‐expiratory occlusion: A pilot study

Abstract: Background and Aims To test the feasibility of a novel, wearable carotid Doppler ultrasound to track changes in cardiac output induced by end‐inspiratory and end‐expiratory occlusion tests. Methods We observed the pattern of Doppler change of the common carotid artery during a simulated end‐inspiratory and expiratory occlusion test (sEIOT/sEEOT) in 10, nonventilated, healthy subjects. Simultaneously, we measured the Doppler signal of the descending aorta using duplex ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…These data are consistent with an earlier feasibility study first describing the DSI using a standardized Valsalva maneuver 7 ; the directional change in carotid Doppler metrics observed during simulated hemorrhage and transfusion was similar to a simulated end‐inspiratory, end‐expiratory occlusion test in healthy volunteers. 21 Although raising intra‐thoracic pressure during a Valsalva maneuver leads to central hypovolemia, the average SV reduction was only about 25% and relatively transient. To better study the effects of moderate‐to‐severe hypovolemia over many minutes, LBNP was employed for the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are consistent with an earlier feasibility study first describing the DSI using a standardized Valsalva maneuver 7 ; the directional change in carotid Doppler metrics observed during simulated hemorrhage and transfusion was similar to a simulated end‐inspiratory, end‐expiratory occlusion test in healthy volunteers. 21 Although raising intra‐thoracic pressure during a Valsalva maneuver leads to central hypovolemia, the average SV reduction was only about 25% and relatively transient. To better study the effects of moderate‐to‐severe hypovolemia over many minutes, LBNP was employed for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We observed an “over‐shoot” in the VTI immediately upon release of LBNP in some volunteers, consistent with our observations in standardized Valsalva maneuvers. 21 This might reflect intra‐cerebral vasodilation that occurs with diminished cerebral perfusion. 22 Indeed, as an exploratory analysis, we compared the common carotid artery resistive index from the wearable Doppler across T1, T2, and T3.…”
Section: Discussionmentioning
confidence: 99%
“…When using oesophageal Doppler, which has the same precision issues as cardiac ultrasound, the combination of EEO and end-inspiratory occlusion can also be used [ 50 ]. It was recently shown that a portable carotid Doppler tool could also track changes in stroke volume during combined end-inspiratory and end-expiratory occlusions [ 51 ], a result that is interesting but needs confirmation.…”
Section: End-expiratory Occlusion Testmentioning
confidence: 99%
“…To address some of these limitations, a wireless, wearable Doppler ultrasound patch that is easily applied over the common carotid artery has been developed (Fig 1, B and C). 64,[72][73][74][75][76] The device (Flosonics Medical, Sudbury, Ontario, Canada) is cleared by both Health Canada and the US Food and Drug Administration. It uses two continuous-wave, 4-MHz ultrasound beams to transmit and receive; the transducers are housed on a wedge that generates a constant angle of insonation of approximately 60˚.…”
Section: Wearable Doppler Ultrasoundmentioning
confidence: 99%
“…Nevertheless, SV changes induced by squatting, passive leg raising, and simulated end-expiratory inspiratory occlusion maneuvers are captured reliably by the wearable carotid ultrasound patch in healthy subjects. 75 Additionally, novel metrics from the wearable ultrasound, such as the Doppler shock index (DSI, heart rate divided by common carotid VTI), might detect falling SV with greater diagnostic accuracy as compared with traditional vital signs. 74 Although the data accumulated with the ultrasound patch were in healthy volunteers, it agreed with data previously described in various patient populations.…”
Section: Carotid Arterial Dopplermentioning
confidence: 99%